Student experiences of multidisciplinarity in the undergraduate geography curriculum. Issue 2 (3rd April 2018) - Hall, Tim; McGuinness, Mark; Parker, Charlotte; Toms, Phil
Abstract: This paper explores the student experience of multidisciplinarity within the undergraduate Geography curriculum. It considers the drivers that have underpinned this development before considering the findings of research into student experiences in two universities in the south of England. The results suggest that most students view this development positively and recognize a number of advantages that it brings, citing expanded opportunities for learning, working with people from other disciplines, expansion of perspectives and perceived benefits to employability. However, for a minority this development is more problematic. The research points here to issues with specialist knowledge and disciplinary pedagogies, social issues within the classroom and class organization and some reservations regarding groupwork. The paper concludes with a series of recommendations.